Answer:
Explanation:
Simplifying
6 + -7x = 7x + -9x + 11
Reorder the terms:
6 + -7x = 11 + 7x + -9x
Combine like terms: 7x + -9x = -2x
6 + -7x = 11 + -2x
Solving
6 + -7x = 11 + -2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '2x' to each side of the equation.
6 + -7x + 2x = 11 + -2x + 2x
Combine like terms: -7x + 2x = -5x
6 + -5x = 11 + -2x + 2x
Combine like terms: -2x + 2x = 0
6 + -5x = 11 + 0
6 + -5x = 11
Add '-6' to each side of the equation.
6 + -6 + -5x = 11 + -6
Combine like terms: 6 + -6 = 0
0 + -5x = 11 + -6
-5x = 11 + -6
Combine like terms: 11 + -6 = 5
-5x = 5
Divide each side by '-5'.
x = -1
Simplifying
x = -1